Status and perspective of protein crystallography at the first multi-bend achromat based synchrotron MAX IV - Ana Gonzalez; Tobias Krojer; Jie Nan; Monika Bjelčić; Swati Aggarwal; Ishkan Gorgisyan; Mirko Milas; Mikel Eguiraun; Cecilia Casadei; Manoop Chenchiliyan; Andrius Jurgilaitis; David Kroon; et al. (Journal of Synchrotron Radiation)
The first multi-bend achromat based synchrotron MAX IV operates two protein crystallography beamlines, BioMAX and MicroMAX. BioMAX is designed as a versatile, stable, high-throughput beamline catering for most protein crystallography experiments. MicroMAX is a more ambitious beamline dedicated to serial crystallography including time-resolved experiments. Both beamlines exploit the special characteristics of fourth-generation beamlines provided by the 3 GeV ring of MAX IV. In addition, the fragment-based drug discovery platform, FragMAX, is hosted and, at the FemtoMAX beamline, protein diffraction experiments exploring ultrafast time resolution can be performed. A technical and operational overview of the different beamlines and the platform is given as well as an outlook for protein crystallography embedded in the wider possibilities that MAX IV offers to users in the life sciences.